Functional Outcome of Vojta Therapy as A Postoperative Protocol for Surgically Treated Patients with Cerebral Palsy - Phongprapapan, Phoemlap; Boontawrach , Jiraporn; Adulkasem , Nath; Eamsobhana, Perajit (Journal of Southeast Asian Orthopaedics, 2023)
Purpose: To evaluate the efficacy of postoperative Vojta therapy in children with cerebral palsy (CP) who have undergone orthopedic surgical interventions for lower limb deformities. Methods: We conducted a prospective case series on children with ambulatory CP aged 3 to 15, indicated for orthopedic surgical interventions (contracture release and deformity correction) between January 2020 and December 2022. One month following these interventions, all patients were scheduled for Vojta therapy sessions. Ambulation capability was evaluated using video gait analysis, an expanded timed get-up-and-go (ETGUG) test, and a 6-minute walk test (6MWT) at 2, 4, and 6 months postoperatively. A multivariable multilevel linear regression analysis was employed to demonstrate the adjusted effect of Vojta therapy during the postoperative period. Results: A total of eleven eligible children with CP were included. Of these, seven were boys (63.6%) with a mean age of 6.3 ± 3.1. The majority of patients were classified as gross motor function classification system (GMFCS) level I (45.4%). We observed a significant improvement in ETGUG (-14.1 sec, p = 0.011), 6MWT (6.3 m, p = 0.014), cadence (2.1 step/min, p = 0.033), and stride time (-0.1 sec, p = 0.027) after being adjusted by baseline function, age, and GMFCS level during the follow-up period. Sub-group analyses revealed no significant difference between patients with GMFCS I and those with GMFCS II to III. Conclusions: This study demonstrated a significant ambulation capability improvement in surgically treated patients with CP who underwent postoperative Vojta therapy.